Cold-formed light gauge steel for rapid deployable shelters - Wu, Hongjun. (2009)
In disaster-prone countries, the victims involved are often left with basic accommodation needs. It takes much time and cost to resettle the victims, giving them basic accommodation for at least a year to two. However, most of the time, funds are limited. Therefore, we need to build shelters which are safe to use and durable. However, cost is often a restraint. In this project, we research on the feasibility of implementing a rapid deployable shelter for the victims after a disaster using cold-formed steel to meet the goals of structurally sound shelters, cost effectiveness and durability.